Higher Regulation, Greater Competition: The Case of Interconnection in the Electricity and Telecommunications Industries - Quiroga, María del Rosario (2015)
This article describes the need of ensure an adequate regulation system in the interconnection matter, looking for having an optimal competency on the different fields of service sectors. Thus, parting from the case of the electricity and telecommunications sectors, it will be verified that, for developing this industries it is necessary to have an adequate regulatory framework in interconnection matter.